THE INFLUENCE OF ZINC CONCENTRATION ON THE DEVELOPMENT AND COURSE OF AUTOIMMUNE THYROIDITIS (International journal of medical sciences, 2026)
Autoimmune thyroiditis (AIT) is one of the most common autoimmune thyroid diseases, leading to hypothyroidism. In recent years, the role of trace elements, particularly zinc, in regulating immune processes and their impact on the development and progression of autoimmune diseases has attracted the attention of researchers. Despite existing data on the importance of zinc in immune homeostasis, antioxidant defense, and thyroid hormone synthesis, its impact on the clinical manifestations of AIT remains understudied. To study the relationship between serum zinc levels and clinical parameters of autoimmune thyroiditis in patients.